FAKTOR YANG MEMPENGARUHI PENGGUNAAN KONTRASEPSI IUD (Intra Uterine Device) DI PUSKESMAS TINGGEDE - Irma, Irma; Syafar, Muhammad Syafar; Azis, Rahmawati; Taurisa, Almaida (Bina Generasi : Jurnal Kesehatan, 2024)
The Family Planning (FP) program has been proven to be one of the most effective efforts to reduce maternal mortality rates. This study aims to identify factors influencing the use of intrauterine device (IUD) contraception in Tinggede Community Health Center, Sigi Regency, Central Sulawesi Province in 2024. The study uses a cross-sectional analytical method with a sample size of 130 FP acceptors at Tinggede Community Health Center. The results show that knowledge, attitude, and the husband's support significantly influence the use of IUD. The higher the knowledge, attitude, and husband's support, the higher the rate of IUD usage. The study also finds that subjective norms do not significantly influence the use of IUD. This indicates that community norms do not greatly affect women's decisions to use IUDs. In conclusion, knowledge, attitude, and the husband's support are important factors influencing the use of IUD at Tinggede Community Health Center, Sigi Regency, Central Sulawesi Province. Therefore, efforts are needed to improve husbands' knowledge and support for IUD to increase the use of this contraceptive method in the community. Keywords: IUD, knowledge, attitude, subjective norms, husband's support